A corrosion model for CZ cladding based on in-pile irradiation data - Duoting, Xu; Xiaoyan, Wei; Xiaohan, Liu; Xin, Jin; Tao, Wang (Frontiers in Energy Research, 2024)
Corrosion resistance is the critical in-pile property for developing new Zircaloy cladding. As a new Zircaloy developed by China General Nuclear Power Corporation, CZ will be used as fuel rod cladding. This study is devoted to investigating the corrosion behavior of CZ. A two-stage Arrhenius equation is proposed to model the corrosion rate. A total of 1,510 measurement data points taken from 151 fuel rods irradiated for 1–4 cycles were used to develop the corrosion model. The burnup of these fuel rods ranges from 13.7 MWd/kgU to 55.9 MWd/kgU. The mean value and standard deviation of P−M (predicted value minus measured value) are 0.54 and 3.65 microns, respectively, and the mean value and standard deviation of P/M (predicted value divided by measured value) are 1.09 and 0.34 microns, respectively. P−M and P/M increase with the local burnup. When the burnup is greater than 40 MWd/kgU, the mean values of P−M and P/M are 6.2 and 1.20 microns, respectively; on the other hand, the prediction of the proposed model is more conservative in high burnup. In the typical case in which the average burnup reaches 57 MWd/kgU, the oxide thickness of CZ cladding is much less than 30 microns, whereas the oxide thickness of Zr-4 cladding is approximately 80 microns, and this manifests that CZ cladding possesses excellent performance in corrosion resistance.